PHYSICAL INACTIVITY, CHRONIC DISEASES, IMMUNITY AND COVID-19 - Guimarães,Thiago Teixeira (2020)
ABSTRACT Complications arising from COVID-19 reflect an abnormal immune response in people previously diagnosed with chronic, non-communicable diseases (NCD), such as cardiovascular, metabolic and pulmonary conditions. Physical inactivity is recognized as a condition that affects the development of chronic low-grade inflammation, NCD, and susceptibility to cell infections. Anxiety and mental stress, poor nutritional status, drug use and circadian rhythm disturbances can further aggravate the harm caused by physical inactivity. Therefore, the purpose of the review is to invite health professionals, their respective regulatory boards, universities, research promotion foundations, media, political authorities and lay citizens to raise awareness of immunity and health in the medium- to long-term control of the current pandemic. Level of evidence V; Expert opinion.